HUBUNGAN ANTARA INDEKS MASSA TUBUH DENGAN KESEIMBANGAN PADA ANAK DOWN SYNDROME DI YPLB NUSANTARA DEPOK - Natasya Shalima David (2023)
Background : In Indonesia there are more than 300.000 children with down syndrome. Down syndrome is a chromosomal abnormality that occurs while still in the womb. Children with down syndrome have a high risk of being overweight or even obese. This increase in BMI causes various problems, one of which is weakening of strength and loss of balance. Research Purposes : To determine the relationship between body mass index (BMI) and balance in children with down syndrome at YPLB Nusantara Depok.. Research Methods : This study used a correlational study design with a cross-sectional approach with a sample of 89 children with Down syndrome. This research was conducted offline by using the pediatric balance scale and measuring body mass index (BMI). Results : This study used SPSS 23 and the results obtained p =0,000 on balance with the correlation coefficient between BMI of 0.559 conclusion there is a unidirectional relationship between BMI and balance. Conclusion Researchs: There is a relationship between body mass index and balance in the same direction in children with down syndrome at YPLB Nusantara Depok.